Illocutionary speech acts in the Instagram account @Fadiljaidi - Dwi Septiani; Viralin Hestiawan; Xie Guilin; Deng Jiao (Lingeduca: Journal of Language and Education Studies, 2023)
An utterance does not only convey the true meaning, but there are other intentions or goals that the speaker wants to achieve when saying something. Therefore, there are utterances in the Instagram account @fadiljaidi which contain illocutionary speech acts. This study uses a qualitative descriptive method. This study uses John's theory. R.Searle. This study uses as many as 50 data. This research was conducted from February to March. Data collection techniques using note-taking techniques. This study uses Searle's theory regarding the types and functions of illocutionary speech. In this study, the types of illocutionary speech acts were: (1) 35 assertive data, (2) 7 directive data, (3) 7 commissive data, (4) 1 expressive data, (5) no declarative data. The function of illocutionary speech acts produces: (1) 26 function data stating, 1 function data showing, 8 function mentioning, (2) 3 data function ordering and 4 data function suggesting, (3) 6 function data praising and 1 function data thanking, (4) 1 data function promising, and (5) declarative function not found.